Comparative Analysis of Soccer and Futsal Extracurriculars: A Survey Study of Physical Fitness Profiles - Didi Suryadi; Mikkey Anggara Suganda; Makan Sacko; Y. Touvan Juni Samodra; Rubiyatno Rubiyatno; Eka Supriatna; Isti Dwi Puspita Wati; Ardo Okilanda (Physical Education and Sports: Studies and Research, 2023)
Background: Futsal and soccer are sports that require endurance and good physical fitness. However, the striking difference, especially in terms of the field used, causes various assumptions. Objectives: The purpose of this study is to compare the levels of physical fitness required for futsal and soccer as extracurricular activities. Methods: The Indonesian Physical Fitness Test (TKJI), In this study, a survey administered to extracurricular football and futsal players aged 13 to 15 was used as a quantitative method. Male students from two separate schools who were involved in extracurricular activities participated in this study, including soccer at State Junior High School 3 Sukadana, and futsal at Madrasah Tsanawiyah State 1 Pontianak. Applying a purposive sampling strategy to collect the sample, 20 futsal extracurricular students and 20 soccer extracurricular students were obtained. The SPSS version 26 program was used to aid in the data analysis for this investigation. Results: According to the study's findings, the average physical fitness score for soccer extracurricular was 15.1, while the average for futsal extracurricular was 11.75. Additionally, the significance value is 0.000 0.05, demonstrating a significant distinction between football and futsal as extracurricular activities. Conclusion: The study on the degree of physical fitness in extracurricular futsal and football found that there is a big gap. These preliminary results might improve understanding of student fitness developments among exercise professionals.